STUDI KOMPARASI PENDAPAT IMAM SYAFI’I DAN IMAM MALIK TENTANG BATAS MINIMAL MASKAWIN - Novi Kurniati; Sudirwan Sudirwan (Fakultas Syariah, Prodi Ahwal As Syakhsiyah (AS) Universitas Nahdlatul Ulama Al-Ghazali (UNUGHA) Cilacap, 2022)
The aim of this research is to determine the minimum dowry limit according to Imam Syafi'i and Imam Malik. This type of research is included in literature or library research (Library Research). The data sources for this research consist of primary data and secondary data. Data analysts use a comparative approach. From the results of this research, it can be seen that according to Imam Syafi'i there is no minimum limit for giving a dowry. Anything that can make it valuable for others can be used as a dowry. For Imam Syafi'i, the main principle in dowry is willingness as in buying and selling, not the nominal amount given. If husband and wife are happy with each other, then both can set a dowry at a small or large level. According to Imam Syafi'i, something that is valuable and acceptable to humans can be used as a dowry, as if the seller and buyer are mutually pleased to carry out a buying and selling transaction on something that has a price, then the transaction is permissible.